Modelagem de cursos à distância via Internet à luz da Ciência da Informação - Duque, Andréa Paula Osório (2001)
This study develops a structured model of distance education taking into consideration the Information Science. It has a conceptual basis on the five principles of Library Science applied to virtual reality. The design of distance education using Internet was based on well known authors of Information Science, Library Science, and Education. It also applies techniques used in cyberspace. The suggested plan - theoretical and applied - contributes to expand the educational potential of distance education using Internet. Using this model, a checklist was designed to help controlling quality of distance education using the Internet.